2022
DOI: 10.3389/fendo.2022.1024759
|View full text |Cite
|
Sign up to set email alerts
|

Exploring risk factors of short-term readmission in heart failure patients: A cohort study

Abstract: BackgroundThe risk of all-cause mortality in patients with heart failure (HF) has been studied previously. Readmission risk of HF patients was rarely explored. Thus, we aimed to explore early warning factors that may influence short-term readmission of HF patients.MethodsThe data of this study came from an HF database in China. It was a retrospective single-center observational study that collected characteristic data on Chinese HF patients by integrating electronic medical records and follow-up outcome data. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…Age as a determinant of readmission remains a topic of debate. Existing literature presents varied conclusions-some suggest improved outcomes with age, others indicate the opposite, and some show no discernible relationship [25][26][27]. Our findings, based on the multivariate analysis, did not identify age as a significant factor for readmission.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Age as a determinant of readmission remains a topic of debate. Existing literature presents varied conclusions-some suggest improved outcomes with age, others indicate the opposite, and some show no discernible relationship [25][26][27]. Our findings, based on the multivariate analysis, did not identify age as a significant factor for readmission.…”
Section: Discussioncontrasting
confidence: 73%
“…Although our study did not delve into the specific reasons for these readmissions, previous research indicated links between early readmissions and conditions such as heart failure, stroke, and COPD [11]. Other determinants of early readmission include high CCI score, prolonged hospitalization, inadequate patient education upon discharge, and medical emergency team (MET) calls [25][26][27]. Interestingly, another Australian retrospective study discovered that factors such as malnutrition, weekday discharge, and Indigenous status increased the risk of early readmission [26].…”
Section: Discussionmentioning
confidence: 84%
“…identified DM, NYHA functional class, serum creatinine, and red cell distribution width (SD) as independent risk factors for heart failure readmission within 6 months. [ 28 ] The mechanisms linking DM to heart failure outcomes involve changes in myocardial structure and energy metabolism. LV concentric remodeling in diabetic myocardium correlates with impaired energy metabolism and reduced myocardial systolic strain.…”
Section: Discussionmentioning
confidence: 99%
“…It is particularly important to note that the co-presentation of DM in patients with HF may predispose them to a worse prognosis. DM was an independent predictor of short-term readmission in a study of 1727 Chinese patients with HF [ 19 ]. DM has been previously established as a severe risk factor for mortality in patients with HF [ 20 ].…”
Section: Epidemiological Trends: Heart Failure and Diabetes Mellitusmentioning
confidence: 99%